INFLAMMATORY PSEUDOTUMOR OF THE LIVER: 3 CASE REPORT AND LITERATURE REVIEW (Tạp chí Y học Cộng đồng, 2022)
Inflammatory pseudotumor of the liver (IPTL) is a rare benign lesion characterizedby chronic infiltration of inflammotory cells and an areas of fibrosis that sometimesmimics a malignant lesion, first reported by Pack and Baker in 1953. The etiologyand pathogy still remain unknown. Clinical and laboratory features are not specific.The treatment attitude is still controversial. We report 3 cases of IPTL who weretreated surgically with preoperative diagnosis of ruptured liver abscess or a malignantliver tumor. The postoperative patient was safe and the pathological results wereinflammotory pseudotumor of the liver. Conclusion: IPTL is a benign lesion thatcan be confused with other diagnoses of the liver. The treatment of choice is stillsurgical resection, and this is especially true for patients with severe symptomsor an indeterminate diagnosis.
Keywords: Inflammatory pseudotumor, the liver, case report